2021
DOI: 10.1177/1558944721990807
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Procedural Medicare Reimbursement Rates in Hand Surgery: 2000 to 2019

Abstract: Background: Medicare reimbursement trends across multiple surgical subspecialties have been analyzed; however, little has been reported regarding the long-term trends in reimbursement of hand surgery procedures. The aim of this study is to analyze trends in Medicare reimbursement for commonly performed hand surgeries. Methods: Using the Centers for Medicare and Medicaid Services Physician and Other Supplier Public Use File, we determined the 20 hand surgery procedure codes most commonly billed to Medicare in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Similar trends have been reported across other surgical specialties and procedures. [3][4][5][6][24][25][26][27][28][29] In addition, Harrington et al 30 found a 7.1% increase in total office visits to neurosurgeons from 2011 to 2018 but an 8.3% inflation-adjusted decrease in the average Medicare reimbursement. Neurosurgeons were billing for more time but were reimbursed a smaller percentage of submitted charges.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends have been reported across other surgical specialties and procedures. [3][4][5][6][24][25][26][27][28][29] In addition, Harrington et al 30 found a 7.1% increase in total office visits to neurosurgeons from 2011 to 2018 but an 8.3% inflation-adjusted decrease in the average Medicare reimbursement. Neurosurgeons were billing for more time but were reimbursed a smaller percentage of submitted charges.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopaedic sports medicine has experienced a similar decrease in reimbursement to other fields of orthopaedic surgery, with the mean inflation-adjusted Medicare reimbursement decreasing 39% for hip and knee arthroplasty, 17 27% for shoulder and elbow surgeries, 28 22.6% for hand surgeries, 40 30% for commonly performed arthroscopy procedures, 29 and 30% for orthopaedic trauma. 19 Accordingly, this study corroborates the findings of decreasing reimbursement found in other subspecialties of orthopaedic surgery and further defines the reimbursement decrease in orthopaedic sports medicine (Appendix Table A2 ).…”
Section: Discussionmentioning
confidence: 99%
“…13,18,20,21,32,33 Furthermore, many orthopaedic surgery subspecialties including total joint replacement, trauma, hand and wrist, and shoulder have reported decreases. 17,19,28,36,40 While these subspecialties have been well defined, there is a paucity of literature regarding Medicare reimbursement in orthopaedic sports medicine. One such applicable study by Moore et al 29 examined arthroscopic procedures and reported a 30% decrease in reimbursement for the included 20 procedures.…”
mentioning
confidence: 99%
“…The data reported in this study are inconsistent with several previous evaluations of monetary trends in plastic surgery. 11,[17][18][19] The current landscape of literature suggests that adjusted Medicare reimbursement is downtrending for various reconstructive procedures, with changes not keeping pace with the rate of inflation. These prior studies coincide with general findings that Medicare payment rates are lagging far behind general inflation and physician practice expenses.…”
Section: Discussionmentioning
confidence: 99%